Analisis Kemampuan Koneksi Matematis Peserta Didik MA Dalam Menyelesaikan Masalah Kontekstual Pada Materi Program Linear - Shely Anisa Husna; Sukoriyanto Sukoriyanto (Jurnal Karya Pendidikan Matematika, 2024)
This study aims to provide an overview of the mathematical connection skills of MA students when solving contextual problems of linear program material. This research applies a qualitative approach and this type of research is descriptive research. The research was conducted at MA Bilingual Batu with the research subjects being students of class XI MIPA1. Students were given mathematical connection ability test questions in the form of contextual problems and based on the test results were grouped into three groups, namely high, medium, and low. Furthermore, from each group one was chosen as the final subject. The research instruments used were mathematical connection ability test questions and interview guidelines. Analysis of the mathematical connection ability of the research subjects was assessed based on indicators of connections with everyday life, connections with other disciplines, and connections between mathematical topics. The results showed that students with high ability could fulfill the indicators of determining plans or strategies, making mathematical models, applying concepts of other disciplines, and determining and applying mathematical concepts to solve the given problem. Learners with moderate mathematical connection ability are only able to fulfill indicators of determining plans or strategies, applying concepts of other disciplines, and determining mathematical concepts to solve given problems. Meanwhile, students with low mathematical connection ability have not been able to fulfill all indicators of aspects of mathematical connection ability.